SETTING UP A DATA ACQUISITION SYSTEM FOR SPARK ENGINES - Ahmed H. Osman; Magdy. M. Massoud (European Scientific Journal, ESJ, 2013)
Measuring dynamic parameters on an engine is very important to diagnose and analysis the faulty problems and the quality of it. To achieve such measurements, it requires expensive data acquisition system (DAS) capable of measuring these parameters. The problem arises when there is a need to build such a system from scratch with a very limited budget and depending on your experience. This paper is dedicated to transfer experience and technology to mechanical engineers who have a little experience in setting up their dynamic test rigs and they do not have enough budgets to buy an expensive DAS [1]. The proposed system is intended to set up a low cost and configurable DAS consisting of sensors, analog to digital card A/D and software package for acquisition and processing. The sensors are used to measure cylinder pressure, vibration of the cylinder block on 3D, different types of temperature (oil, inlet and outlet water temperature), crank angle and engine’s RPM. The processing includes cycle separation to prepare the acquired data for heat release analysis. The Fast Fourier Transformation (FFT) is also used to analyze the data for fault diagnosis using vibration analysis. The developed system saves about 75% of the price of a similar on the shelve system.